2011
DOI: 10.1007/s13204-011-0016-1
|View full text |Cite|
|
Sign up to set email alerts
|

Functional role of cationic surfactant to control the nano size of silica powder

Abstract: Preparation of dispersed, amorphous, spherical silica nanoparticles using cationic surfactant as organic template, tetraethoxysilane (TEOS) as silica precursor and ammonia as catalyst has been carried out using sol gel process. The aim of the present study was to evaluate the simultaneous effects of cationic surfactant on the textural and structural properties of silica nanoparticles. We used a series of the cationic surfactants, dodecytrimethylammonium bromide (DTAB), tetradecyltrimethylammonium bromide (TTAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 18 publications
2
40
0
1
Order By: Relevance
“…It has been reported that nanosilica (NS) have a significant impact on accelerating the hydration process of cement (Singh et al 2011;Land and Stephan 2012;Skoczylas and Rucińska 2018a), refining the pore structure of cement matrices (Sikora et al 2016), improving early and long-term mechanical properties (Skoczylas and Rucińska 2018b), as well as improving the durability performance Submitted to special issue NANO-2018 within the 6th International Conference "Nanotechnologies and Nanomaterials" NANO-2018. of cementitious composites (Du et al 2014;Heikal et al 2016;Marushchak et al 2017). The beneficial effect of silica nanoparticles is attributable to three synergistic effects: (i) the filler effect-nanosized silica particles fill the voids in the cement matrix, decreasing paste porosity and optimizing the distribution of the pore structure; (ii) the nucleation effect-ultrafine silica nanoparticles act as the nucleation sites (kernels) for the hydration reaction of the cement; (iii) the pozzolanic effect-through the reaction of silica nanoparticles with calcium hydroxide (CH), the amount of calcium silicate hydrate (C-S-H) gel increases (Singh et al 2011(Singh et al , 2013Abd El-Aleem and Ragab 2014;El-Didamony et al 2016;Маrushchak et al 2016;Xu et al 2016;Rupasinghe et al 2017). The effects of NS on the properties of cement-based composites have been investigated in detail in recent years and many review papers are available (Singh et al 2013;Safiuddin et al 2014;Aggarwal et al 2015;Silvestre et al 2015;Shah et al 2015;Bastos et al 2016;Sikora et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that nanosilica (NS) have a significant impact on accelerating the hydration process of cement (Singh et al 2011;Land and Stephan 2012;Skoczylas and Rucińska 2018a), refining the pore structure of cement matrices (Sikora et al 2016), improving early and long-term mechanical properties (Skoczylas and Rucińska 2018b), as well as improving the durability performance Submitted to special issue NANO-2018 within the 6th International Conference "Nanotechnologies and Nanomaterials" NANO-2018. of cementitious composites (Du et al 2014;Heikal et al 2016;Marushchak et al 2017). The beneficial effect of silica nanoparticles is attributable to three synergistic effects: (i) the filler effect-nanosized silica particles fill the voids in the cement matrix, decreasing paste porosity and optimizing the distribution of the pore structure; (ii) the nucleation effect-ultrafine silica nanoparticles act as the nucleation sites (kernels) for the hydration reaction of the cement; (iii) the pozzolanic effect-through the reaction of silica nanoparticles with calcium hydroxide (CH), the amount of calcium silicate hydrate (C-S-H) gel increases (Singh et al 2011(Singh et al , 2013Abd El-Aleem and Ragab 2014;El-Didamony et al 2016;Маrushchak et al 2016;Xu et al 2016;Rupasinghe et al 2017). The effects of NS on the properties of cement-based composites have been investigated in detail in recent years and many review papers are available (Singh et al 2013;Safiuddin et al 2014;Aggarwal et al 2015;Silvestre et al 2015;Shah et al 2015;Bastos et al 2016;Sikora et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The increase of template agent chain length from 12 to 16 methyl groups results in increasing of the pore mean diameter [12,16]. The two dimension parameters may also correlate: in an ammonia catalyzed synthesis, the particle size decreased as the chain length of the surfactant increased [17].…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 6(i), representing the azide functionalized SiNPs, shows a broad peak centred at 2h = 22.4°(d-spacing at 3.96), while the confirms the amorphous nature of the SiNPs, which is maintained after functionalization [31,32].…”
Section: Xrd Spectral Characterizationmentioning
confidence: 63%